Progress of alveolar macrophages in biological function and acute lung injury/acute respiratory distress syndrome - Yan, Mi; Tang, Jia; Liu, Yanfei; Hu, Zhangxue (Frontiers in Immunology, 2025)
Alveolar macrophages (AMs), a type of immune cell, display remarkable plasticity and manifest diverse responses to stimuli by differentiating into distinct subgroups. These phenotypically distinct macrophage subtypes are primarily categorized as either classically activated or inflammatory (M1) macrophages, or alternatively activated or anti-inflammatory (M2) macrophages, the differentiation of which is underpinned by a complex regulatory network. Despite their crucial contribution to the pathobiology of acute lung injury/acute respiratory distress syndrome (ALI/ARDS), the research on AMs is currently limited. This study therefore aims to establish a comprehensive theoretical framework delineating the pathogenic role of AMs in ALI/ARDS, facilitating deeper mechanistic understanding of disease initiation and progression in ALI/ARDS and ultimately identifying novel therapeutic targets.